KUPRAVA CLAY DEPOSIT RESEARCH COMPARISON (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Clay minerals and their structures are extensively studied in the world, both from the point of view of geological research and material science. The aim of the research is to identify and summarize the resources of the Kuprava clay deposit, their placement in the field and selective extraction possibilities. Total clay resources in the Kuprava area are significantly more than 16 million m³. The clays are located in several uneven layers with relatively different characteristics. Until now, clay has been studied in separate layers for the production of bricks and high quality lightweight expanded clay aggregate (LECA). The work is based on using and comparing the geological survey data of 1951 to 1992, the latest laboratory test data, as well as the technical documentation of the former Kuprava factory. The study also includes a review of two recent studies of the composition of Kuprava Member clay. New eco-innovative composite materials require clay with a fully defined composition and properties. Clay extraction must be selective - on separate layers, so that the use can be accurately determined by the research. Cartographic material has also been added to accurately locate each of the four fields studied.